The Use Of Poetry In Teaching Pronunciation; An Experimental Study At The Second GradeStudents Of Ma Tahzibul Akhlak Sisik In Academic Year - Jumatriadi, Jumatriadi (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2014)
This study investigates the use of poetry in teaching pronunciation. The method used in this study was quantitative and qualitative descriptive study. The population of this study was all of the second grade students of MA Tahzibul Akhlak Sisik In Academic Year 2014/2015. The sample of this study was 40 students. The technique that was used to collect the data was test. The data that are needed in this study is the result of post-test. Based on the data gained for experimental group in gained the lowest and the highest score 32 and 88. For the control group gained the lowest and highest score 20 and 66. The result of data analysis is indicated that the figure of the means score was 47,1 for experimental group and 35,9 for control group. The deviation scores for experimental group was 156,89 and control group was 197,39. Itâs means that after treatment by using poetry there was a positively significant in teaching pronunciation